Identifying the best fishing-suitable areas under the new European discard ban. (14th July 2016) - Paradinas, Iosu; Marín, Marcial; Grazia Pennino, Maria; López-Quílez, Antonio; Conesa, David; Barreda, David; Gonzalez, Maria; María Bellido, José; ,
Abstract: The spatial management of fisheries has been repeatedly proposed as a discard mitigation measure. A number of studies have assessed the fishing suitability of an area based on units of by-catch or discard per unit effort. However, correct identification of fishing-suitable areas should assess biomass loss with respect to the benefits. This study therefore, proposes the analysis of by-catch ratios, which do represent benefit vs. loss and are standardized to a wide range of effort characteristics. Furthermore, our study proposes the use of two ratios: the proportion of total unwanted biomass out of the total catch as an indicator of the overall ecological impact, and the proportion of unwanted but regulated species biomass as a proxy for the economic impact on fishers resulting from the new European discard ban that prohibits the discard of regulated species. These discard ratios are modelled by means of a Bayesian hierarchical model, specifically, a spatio-temporal beta regression model, which has several advantages over the traditional arcsine transformation. Results confirm the standardizing capacity of by-catch ratios across vessels and identify at least two economically fishing-suitable areas where discards ratios are minimized by reducing unwanted catch.